The impact of patient factors on use of antifungal medicines in adults with life-threatening illness: a cross-sectional study in 34 English hospitals. Issue 1 (1st August 2014) - Stephens, Peter; Chikh, Karim; Leufkens, Hubert
Abstract : Objectives: To describe the use of antifungal medicines in English hospitals in adults with life-limiting illness and to investigate the association between socio-demographic variables and the use of high-cost formulations. Methods: Pseudonymised patient-level information extracted from hospital pharmacy systems in 34 English acute general hospitals was linked to a National Health Service database of diagnoses and procedures. National Information Governance Board for England and Ethics approval was granted. The impact of socio-demographic variables on the use of high-cost formulations was assessed using stepwise logistic regression across 13 disease groups. Hospital guidelines on the use of antifungals were sourced and compared. Results: People with haematological malignancies and unconfirmed infection formed the largest disease group (49.3%). Fungal infection was confirmed in an additional 12.6%. Guidelines focused on antifungal use in neutropenic patients. No guideline cited patient age, deprivation, gender or ethnicity as independent factors influencing treatment. Fluconazole dominated use (75% admissions). Significant associations were found between age, gender, deprivation and ethnicity and the use of high-cost antifungals. However, the direction of that association was not consistent across disease groups. Conclusions: This study found widespread use of fluconazole, echoing results of earlier studies across Europe. It also found associations between patient factors and high-cost antifungal use that are not easily explained by disease, comorbidities, contraindications, guidelines or any systematic bias against particular groups of patients. It is clear that the drivers of antifungal therapy in hospital are complex and that antifungal stewardship poses a significant challenge for pharmacy.